Αντισεισμική ενίσχυση υφισταμένου κτιρίου - Χριστοφή, Αντώνης (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας ,Τεχνολογικό Πανεπιστήμιο Κύπρου., 2015)
The aim of this project is to retrofit a 1980’s structure for seismic loads using the software 3DR STRAD PRO 2014. Initially, the seismic resistance of the building is assessed, followed by the strengthening using fiber reinforced polymer composites and concrete jackets. The first chapter summarizes various methods for resisting earthquake loads using various methods of intervention. The second chapter is concerned with the necessary checks that enable the determination of the properties of materials and provide an initial assessment of the structure. The third chapter explores the methods of analysis, linear and non-linear, with emphasis on the non-linear static analysis (push-over analysis). The fourth chapter describes two retrofitting methods for enhancing seismic resistance. Namely, the method of fiber reinforced polymer composites and the method of concrete jackets. In the fifth chapter, the case-study building is presented. The description includes material strengths, member sizes and reinforcement details that are needed for the modeling of the structure. The sixth chapter presents the results of the linear and non-linear method. Based on these results the decision on which parts will be strengthened is made. In the seventh chapter a discussion of the seismic retrofitting of the structure is presented along with some general conclusions.
Keywords: Seismic loads; Software 3DR STRAD PRO 2014; Seismic resistance; Methods of intervention; Linear analysis; Non-linear analysis; Aντισεισμική ενίσχυση; Λογισμικο 3DR STRAD PRO 2014; Μανδύας οπλισμένου σκυροδέματος; Σεισμικό φορτίο; Ελαστική μέθοδος ανάλυσης; Ανελαστική μέθοδος ανάλυσης